Electricity and Magnetism New Formulation by Introduction of Superconductivity - Matsushita, Teruo (Undergraduate Lecture Notes in Physics,, 2014)
The author introduces the concept that superconductivity can establish a perfect formalism of electricity and magnetism. The correspondence of conductors that exhibit perfect electrostatic shielding (E=0) in the static condition and superconductors that show perfect diamagnetism (B=0) is given to help readers understand the relationship between electricity and magnetism. Another helpful aspect with the introduction of the superconductivity feature perfect diamagnetism is that the correspondence in the development of the expression of magnetic energy and electric energy is clearly shown. Additionally, the basic mathematical operation and proofs are shown in an appendix, and there is full use of examples and exercises in each chapter with thorough answers.